STRUCTURE OF HEAVY METAL SORBED BIRNESSITE. PART III: RESULTS FROM POWDER AND POLARIZED EXTENDED X-RAY ABSORPTION FINE STRUCTURE SPECTROSCOPY - Manceau A.; Lanson B.; Drits V.A. (My University, 2002)
The local structures of divalent Zn, Cu, and Pb sorbed on the phyllomanganate birnessite (Bi) have been studied by powder and polarized extended X-ray absorption fine structure (EXAFS) spectroscopy. Metal-sorbed birnessites (MeBi) were prepared at different surface coverages by equilibrating at pH 4 a Na-exchanged buserite (NaBu) suspension with the desired aqueous metal. Me/Mn atomic ratios were varied from 0.2% to 12.8% in ZnBi and 0.1 to 5.8% in PbBi. The ratio was equal to 15.6% in CuBi. All cations sorbed in interlayers on well-defined crystallographic sites, without evidence for sorption on layer edges or surface precipitation. Zn sorbed on the face of vacant layer octahedral sites (□), and shared three layer oxygens (Olayer) with three-layer Mn atoms (Mnlayer), thereby forming a tridentate corner-sharing (TC) interlayer complex (Zn-3Olayer-□-3Mnlayer). TCZn complexes replace interlayer Mn2+ (Mninter2+) and protons. TCZn and TCMninter3+ together balance the layer charge deficit originating from Mnlayer4+ vacancies, which amounts to 0.67 charge per total Mn according to the structural formula of hexagonal birnessite (HBi) at pH 4. At low surface coverage, zinc is tetrahedrally coordinated to three Olayer and one water molecule ([IV]TC complex: (H2O)-[IV]Zn-3Olayer). At high loading, zinc is predominantly octahedrally coordinated to three Olayer and to three interlayer water molecules ([VI]TC complex: 3(H2O)-[VI]Zn-3Olayer), as in chalcophanite ([VI]ZnMn34+O7·3H2O). Sorbed Zn induces the translation of octahedral layers from −a/3 to +a/3, and this new stacking mode allows strong H bonds to form between the [IV]Zn complex on one side of the interlayer and oxygen atoms of the next Mn layer (Onext): Onext…(H2O)-[IV]Zn-3Olayer. Empirical bond valence calculations show that Olayer and Onext are strongly undersaturated, and that [IV]Zn provides better local charge compensation than [VI]Zn. The strong undersaturation of Olayer and Onext results not only from Mnlayer4+ vacancies, but also from Mn3+ for Mn4+ layer substitutions amounting to 0.11 charge per total Mn in HBi. As a consequence, [IV]Zn,Mnlayer3+, and Mnnext3+ form three-dimensional (3D) domains, which coexist with chalcophanite-like particles detected by electron diffraction. Cu2+ forms a Jahn-Teller distorted [VI]TC interlayer complex formed of two oxygen atoms and two water molecules in the equatorial plane, and one oxygen and one water molecule in the axial direction. Sorbed Pb2+ is not oxidized to Pb4+ and forms predominantly [VI]TC interlayer complexes. EXAFS spectroscopy is also consistent with the formation of tridentate edge-sharing ([VI]TE) interlayer complexes (Pb-3Olayer-3Mn), as in quenselite (Pb2+Mn3+O2OH). Although metal cations mainly sorb to vacant sites in birnessite, similar to Zn in chalcophanite, EXAFS spectra of MeBi systematically have a noticeably reduced amplitude. This higher short-range structural disorder of interlayer Me species primarily originates from the presence of Mnlayer3+, which is responsible for the formation of less abundant interlayer complexes, such as [IV]Zn TC in ZnBi and [VI]Pb TE in PbBi.